Gastrointestinal immune and microbiome changes during parenteral nutrition - Pierre, Joseph F. (Am J Physiol Gastrointest Liver Physiol, 2017)
Parenteral nutrition (PN) is a lifesaving therapy that provides intravenous nutrition support to patients who cannot, or should not, feed via the gastrointestinal (GI) tract. Unfortunately, PN also carries certain risks related to infection and metabolic complications compared with enteral nutrition. In this review, an overview of PN and GI immune and microbiome changes is provided. PN impacts the gut-associated lymphoid tissue functions, especially adaptive immune cells, changes the intestinal epithelium and chemical secretions, and significantly alters the intestinal microbiome. Collectively, these changes functionally result in increased susceptibility to infectious and injurious challenge. Since PN remains necessary in large numbers of patients, the search to improve outcomes by stimulating GI immune function during PN remains of interest. This review closes by describing recent advances in using enteric nervous system neuropeptides or microbially derived products during PN, which may improve GI parameters by maintaining immunity and physiology.